New insight into the application of fluorescence platforms in tumor diagnosis: From chemical basis to clinical application. Issue 3 (24th November 2022) - Li, Yanchen; Chen, Qinhua; Pan, Xiaoyan; Lu, Wen; Zhang, Jie
Abstract: Early and rapid diagnosis of tumors is essential for clinical treatment or management. In contrast to conventional means, bioimaging has the potential to accurately locate and diagnose tumors at an early stage. Fluorescent probe has been developed as an ideal tool to visualize tumor sites and to detect biological molecules which provides a requirement for noninvasive, real‐time, precise, and specific visualization of structures and complex biochemical processes in vivo. Rencently, the development of synthetic organic chemistry and new materials have facilitated the development of near‐infrared small molecular sensing platforms and nanoimaging platforms. This provides a competitive tool for various fields of bioimaging such as biological structure and function imaging, disease diagnosis, in situ at the in vivo level, and real‐time dynamic imaging. This review systematically focused on the recent progress of small molecular near‐infrared fluorescent probes and nano‐fluorescent probes as new biomedical imaging tools in the past 3–5 years, and it covers the application of tumor biomarker sensing, tumor microenvironment imaging, and tumor vascular imaging, intraoperative guidance and as an integrated platform for diagnosis, aiming to provide guidance for researchers to design and develop future biomedical diagnostic tools.